Icariin Enhances Bone Repair in Rabbits with Bone Infection during Post-infection Treatment and Prevents Inhibition of Osteoblasts by Vancomycin - Zhang, Yang; Shen, Lifeng; Mao, Zhujun; Wang, Nani; Wang, Xuping; Huang, Xiaowen; Hu, Ying; Shou, Dan; Wen, Chengping (Frontiers in Pharmacology, 2017)
Vancomycin is an effective antibiotic for treatment of bone infection caused by Staphylococcus aureus (S. aureus), however, a high local concentration of vancomycin might induce a delay in bone union. Icariin has been reported to suppress osteoclastogenes and promote osteogenesiso. Our study aimed to investigate the effect of icariin on bone repair after anti-infection treatment in vivo and to explore the resisting effect of icariin on rat calvarial osteoblasts (ROBs) inhibited with high doses of vancomycin. Rabbits with bone infection of S. aureus were treated with implanted vancomycin-calcium sulphate (VCS) and icariin at 10.86 mg/kg/day for consecutive 8 weeks. Micro-CT, morphology, blood biochemistry were evaluated. In addition, ROBs were treated with vancomycin and icariin at different doses. Cell proliferation and differentiation capabilities, BMP2, Runx2, OPG, RANKL mRNA levels and protein expression were assessed. Our results indicated that high dose of vancomycin significantly decreased bone mass and inhibited osteocalcin secretion; icariin increased these indicators compared with the single vancomycin treatment. Over 0.1 mg/mL of vancomycin inhibited the proliferation and differentiation of ROBs, while icariin resisted the inhibition of vancomycin by regulating cell cycle and promoting the Alkaline phosphatase (ALP) activity. Moreover, icariin promote bone formation by up-regulating BMP2/Runx2 and OPG/RANKL pathways.